The Availability of Health Resources on the Performance of Maternal and Child Health Policy Implementation in East Nusa Tenggara - Florentianus Tat; Irfan Irfan; Maria Magdalena Bait (Global Medical & Health Communication (GMHC), 2020)
Maternal and child health problems continue to be priority health issues in Indonesia, especially in East Nusa Tenggara (NTT). The maternal mortality rate in NTT has reached 159/100,000 live births, while infant and under-five mortality rates have reached 32/1000 live births and 40/1,000 live births, respectively above the national value of 23/1000 live births and 32/1,000 live births. It indicates that the health and maternal and child health policies in NTT have not been maximally implemented. One of the causes is the lack of available health worker resources that provide health services. The research objective is to identify the effect of health resources' availability on the performance of maternal and child health policy implementation in NTT. A quantitative research method for data collection was carried out in 11 districts in NTT and 104 public health centers (pusat kesehatan masyarakat, puskesmas) towards 235 health workers from August to December 2019. The results show that the health workers were categorized as insufficient/not available (mean value of 2.64), and puskemas did not have doctors, midwives, and nurses conforming to standards. There was also inadequacy in some aspects such as budget (average value of 2.45), medical devices (average value of 2.75), medicines and medical supplies, buildings, and transport. A correlation was found between resources and the performance of maternal and child health policies (p=0.00) with a coefficient correlation of 0.546. It indicates a strong and positive correlation, which means that if there is an increase in resources, maternal and child health policy implementation will also. Partial linear regression tests showed t arithmetic=13.304 >t table 1.97, which means that H0 was rejected. It suggests a significant effect between resources and the performance of maternal and child health policy implementation in NTT. In conclusion, resources had a positively impact on the performance of maternal and child health policy in NTT. PENGARUH KETERSEDIAAN SUMBER DAYA KESEHATAN TERHADAP KINERJA IMPLEMENTASI KEBIJAKAN KESEHATAN IBU DAN ANAK DI NUSA TENGGARA TIMURPermasalahan kesehatan ibu dan anak (KIA) terus menjadi prioritas masalah kesehatan di Indonesia khususnya di Nusa Tenggara Timur (NTT). Angka kematian ibu di NTT mencapai 159/100.000 kelahiran hidup (KH), sedangkan angka kematian bayi dan balita mencapai 32/1.000 KH dan 40/1.000 KH yang masing-masing di atas nilai nasional, yaitu 23/1.000 KH dan 32/1.000 KH. Kondisi tersebut mengindikasikan bahwa penerapan kebijakan KIA di NTT belum dilaksanakan secara maksimal. Salah satu penyebabnya adalah sumber daya manusia kesehatan yang memberikan pelayanan kesehatan kurang tersedia. Tujuan penelitian adalah mengidentifikasi pengaruh ketersediaan sumber daya manusia kesehatan terhadap kinerja penerapan kebijakan KIA di NTT. Metode penelitian adalah kuantitatif. Pengumpulan data dilakukan di 11 kabupaten dan 104 pusat kesehatan masyarakat (puskesmas) pada 235 tenaga kesehatan dari bulan Agustus hingga Desember 2019. Hasil penelitian menunjukkan bahwa tenaga kesehatan dikategorikan tidak cukup/tidak tersedia (nilai rerata 2,64) dan puskesmas tidak memiliki dokter, bidan, dan perawat sesuai standar. Selain itu, terdapat juga kekurangan di beberapa aspek seperti anggaran biaya (nilai rerata 2,45), alat kesehatan (nilai rerata 2,75), obat dan perbekalan kesehatan, alat medis, bangunan, serta alat transportasi. Korelasi ditemukan antara sumber daya dan kinerja penerapan kebijakan KIA (p=0,00) dengan koefisien korelasi 0,546. Hal ini berarti korelasi cukup kuat dan positif, artinya jika sumber daya ditingkatkan maka kinerja implementasi kebijakan KIA juga meningkat. Uji regresi linier parsial menunjukkan t hitung=13,304 >t tabel 1,97 yang bermakna H0 ditolak. Hal ini menunjukkan pengaruh yang signifikan antara sumber daya dan kinerja penerapan kebijakan KIA di Provinsi NTT. Simpulan, sumber daya berpengaruh positif terhadap kinerja penerapan kebijakan KIA di NTT.